The Relationship Between The Role Of Parents And Children In The Prevention Of Pneumonia To Toddlers At Rejosari Health Center Pekanbaru City - Pinondang Hotria Siregar (Universitas Dharma Wacana, 2022)
This study aims to determine the relationship between the role of parents and children in the prevention of pneumonia in children under five at the Rejosari Health Center, Pekanbaru City. Research results Based on the results of the analysis showed that there was a relationship between parental behavior and the rate of recurrence of pneumonia in toddlers, so it can be said that if parents behaved well then pneumonia experienced by toddlers tended not to recur and vice versa if the behavior of parents was lacking then pneumonia experienced by toddlers tend to recur. Researchers argue that the condition of toddlers is still vulnerable to health problems and is still very dependent on parents to prevent pneumonia. One of the behaviors of parents in preventing pneumonia recurrence is the habit of opening windows, this will make it easier for light and air circulation into the house. Other parental actions that can play a role in preventing a recurrence of pneumonia include keeping toddlers away from someone who smokes. The air pollution released prevents the recurrence of pneumonia by someone who smokes, for example opening a window every day. As a respondent, it is necessary to further improve behavior in toddlers with pneumonia to avoid recurrence and consult health workers so that it does not get worse so that it can be prevented as early as possible. For health workers to provide counseling and counseling, especially to parents about good behavior in caring for toddlers with pneumonia at home. Other parental actions that can play a role in preventing the recurrence of pneumonia include keeping toddlers away from someone who smokes. The air pollution released prevents the recurrence of pneumonia by someone who smokes, for example opening a window every day. As a respondent, it is necessary to further improve behavior in toddlers with pneumonia to avoid recurrence and consult health workers so that it does not get worse so that it can be prevented as early as possible.Â